Cytoplasmic Dynein Light Intermediate Chain Is Required for Discrete Aspects of Mitosis in Caenorhabditis elegans - Yoder, John H. (The American Society for Cell Biology, 2001)
We describe phenotypic characterization of dli-1, the Caenorhabditis elegans homolog of cytoplasmic dynein light intermediate chain (LIC), a subunit of the cytoplasmic dynein motor complex. Animals homozygous for loss-of-function mutations in dli-1 exhibit stochastic failed divisions in late larval cell lineages, resulting in zygotic sterility. dli-1 is required for dynein function during mitosis. Depletion of the dli-1 gene product through RNA-mediated gene interference (RNAi) reveals an early embryonic requirement. One-cell dli-1(RNAi) embryos exhibit failed cell division attempts, resulting from a variety of mitotic defects. Specifically, pronuclear migration, centrosome separation, and centrosome association with the male pronuclear envelope are defective in dli-1(RNAi) embryos. Meiotic spindle formation, however, is not affected in these embryos. DLI-1, like its vertebrate homologs, contains a putative nucleotide-binding domain similar to those found in the ATP-binding cassette transporter family of ATPases as well as other nucleotide-binding and -hydrolyzing proteins. Amino acid substitutions in a conserved lysine residue, known to be required for nucleotide binding, confers complete rescue in a dli-1 mutant background, indicating this is not an essential domain for DLI-1 function.